2018
DOI: 10.1029/2017wr022163
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Climate Variability on Snowmelt and Implications for Organic Matter in a High‐Elevation Lake

Abstract: Few coupled lake‐watershed studies examine long‐term effects of climate on the ecosystem function of lakes in a hydrological context. We use 32 years of hydrological and biogeochemical data from a high‐elevation site in the Sierra Nevada of California to characterize variation in snowmelt in relation to climate variability and explore the impact on factors affecting phytoplankton biomass. The magnitude of accumulated winter snow, quantified through basinwide estimates of snow water equivalent (SWE), was the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 60 publications
1
57
0
Order By: Relevance
“…A key feature of high elevation lakes in the SRM is that they are distinctly snowmelt driven systems (Hauer et al ). It appears that melting snowpack in the spring and perennial ice/snow during summer have buffered lakes in our region against surface warming, similarly to other high elevation regions (Zhang et al ; Sadro et al ). But snowpack in our region is diminishing and melting earlier, while glaciers are receding (Hoffman et al ; Clow ) so lake warming patterns may undergo another abrupt change in the future.…”
Section: Discussionsupporting
confidence: 73%
“…A key feature of high elevation lakes in the SRM is that they are distinctly snowmelt driven systems (Hauer et al ). It appears that melting snowpack in the spring and perennial ice/snow during summer have buffered lakes in our region against surface warming, similarly to other high elevation regions (Zhang et al ; Sadro et al ). But snowpack in our region is diminishing and melting earlier, while glaciers are receding (Hoffman et al ; Clow ) so lake warming patterns may undergo another abrupt change in the future.…”
Section: Discussionsupporting
confidence: 73%
“…Although temperature was not included in the mixed modeling due to collinearity with other variables, in years when Sierra snowpack was deep, such as 2017 when April 1 SWE was ∼ 200% of normal, Sierra lake temperature rose 1°C month −1 slower than in a drought year, and peaked at a slightly lower temperature than in low snow years (Sadro et al ). Thus in drought years, higher temperatures will drive gas solubility lower than in a deep snowpack year, which would cause additional evasion, but this is mediated by the length of the ice‐covered period, a direct result of SWE.…”
Section: Discussionmentioning
confidence: 99%
“…For high‐elevation lakes within the Sierra, watershed snow water equivalent (SWE) determines the timing of ice‐off in spring (Sadro et al ), which sets the length of time during which CO 2 can accumulate under ice. In addition, SWE is negatively correlated with summer dissolved organic carbon (DOC) concentrations (Sadro et al ), and an increase in DOC inputs was observed to shift a southern Sierra lake to net heterotrophy (Sadro et al ) by increasing allochthony. Late summer p CO 2 across a latitudinal gradient of lakes throughout the Sierra in 2014 (S. Sadro, pers.…”
Section: Characteristics Of Each Sampled Lake (L) or Reservoir (R); Lmentioning
confidence: 99%
“…Small changes in water temperature are known to affect biological processes and ecosystem function in mountain lakes (Parker et al 2008;Miller and McKnight 2015;Preston et al 2016). In the Sierra, snowpack controls on the timing of nutrient delivery and warming have important implications for phytoplankton biomass (Sadro et al 2018). Our study suggests that Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Just as importantly, the proportion of precipitation falling as snow in many mountain regions is declining (Lundquist et al 2009;Berg and Hall 2017). Because they have distinct hydrological patterns driven by the deposition and subsequent melt of winter snowpack (Lundquist et al 2009;Sadro et al 2018), the potential impact on lake heat budgets may be substantial (Strub et al 1985). Finally, there are large gradients in local landscape and lake morphometric features in mountains that are expected to mediate the effect of climate warming (Livingstone et al 2005;Sadro et al 2012).…”
mentioning
confidence: 99%